Total Phenolic Exudation and Allelopathic Potential of Sunflower Residues as Sustainable Weed Management - Flayyih, Taisir M.; Almarie, Ahmed A. (Iraqi Journal of Science, 2023)
Total releasing phenolic compounds and allelopathic potential of the three sunflower genotypes Helianthus annuus L. residues were evaluated under open field conditions on weed flora associated with the proposed crops; wheat, broad bean and flax which are cultivated usually after the sunflower crop as successive crops. After getting seed from the sunflower crop. After getting seeds, sunflower plant parts were chopped and incorporated with field soil using a rotavator. Regarding the phenolics, total phenolic compounds released from sunflower residues were increased in-field soil and reached the highest concentration in the fourth week after mixing with soil. Significant suppression of weed flora was observed when the weed density and weed dry matter were reduced. Sakha sunflower genotype had the most effect, while Ishaqi genotype had the least amount of phenolic compounds. The residue of the Sakha genotype effectively suppressed over 80% of targeted weeds. The results indicate that the allelopathic potential of sunflower residues can cause suppression of weed flora which can be useful as an attractive alternative natural way to reduce synthetic herbicides as sustainable weed management.